Effect of laser shock peening on bending fatigue performance of AISI 9310 steel spur gear. (1st September 2017) - Peng, Chong; Xiao, Yuzhe; Wang, Yanzhong; Guo, Wei
Highlights: Residual compressive stress can be induced on gear root surface. Bending fatigue lives of gear teeth can be significantly improved. Higher laser energy may not bring much better fatigue performance of test gears. Abstract: The effect of laser shock peening (LSP) on bending fatigue performance of AISI 9310 steel spur gear has been investigated in this study. To help to explain bending fatigue test results, residual stress distribution induced by LSP is studied by means of finite element modelling, results of which are verified by X-ray diffraction analysis. It is found that a compressive layer of desirable depth can be induced on the gear root fillet after LSP, and both magnitude and depth of compressive stress increase with laser energy. The bending fatigue test is conducted using the single-tooth bending method to compare fatigue performance of laser peened teeth and non-peened teeth, which is followed by relevant statistical analysis. S-N curves acquired from the fatigue test reveal that bending fatigue lives of gear teeth has been significantly improved after LSP in comparison with those non-peened teeth, and the bending fatigue limit is enhanced correspondingly. It is noticeable that higher laser energy does not necessarily lead to much better fatigue performance of test gears.